2012
DOI: 10.1523/jneurosci.6216-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between Electrical Coupling and Membrane Properties Promotes Strong Synchronization of Neurons of the Mesencephalic Trigeminal Nucleus

Abstract: Electrical synapses are known to form networks of extensively coupled neurons in various regions of the mammalian brain. The mesencephalic trigeminal (MesV) nucleus, formed by the somata of primary afferents originating in jaw-closing muscles, constitutes one of the first examples supporting the presence of electrical synapses in the mammalian CNS, however, the properties, functional organization and developmental emergence of electrical coupling within this structure remain unknown. By combining electrophysio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
227
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(250 citation statements)
references
References 84 publications
23
227
0
Order By: Relevance
“…Fukuda et al [2006] mention that about 2-5% of Cx36 spots in the visual cortex indicate functional gap junctions. This is in rough accordance with the estimations of Curti et al [2012] that only about 0.1% of gap junction channels are functional and in the open configuration, under the assumption that each Cx36 spot includes tens to hundreds of gap junction channels Zukin, 2004, Bukauskas et al, 2000]. Supposing that this ratio is similar for GPe, i.e.…”
Section: Estimated Connectivity Within the External Part Of The Globusupporting
confidence: 88%
See 1 more Smart Citation
“…Fukuda et al [2006] mention that about 2-5% of Cx36 spots in the visual cortex indicate functional gap junctions. This is in rough accordance with the estimations of Curti et al [2012] that only about 0.1% of gap junction channels are functional and in the open configuration, under the assumption that each Cx36 spot includes tens to hundreds of gap junction channels Zukin, 2004, Bukauskas et al, 2000]. Supposing that this ratio is similar for GPe, i.e.…”
Section: Estimated Connectivity Within the External Part Of The Globusupporting
confidence: 88%
“…Firstly, detection of Cx36 on cell membranes does not directly imply gap junction coupling, but can also indicate hemi-channels or non-functional gap junctions. Fukuda et al [2006] mentioned that 2-5% of Cx36 spots indicate functional gap junctions in the open configuration, whereas Curti et al [2012] estimate about 0.1% of Cx36 spots to be open, functional gap junctions. In pathological states such as PD, the average function of the gap junctions may change.…”
Section: Discussionmentioning
confidence: 99%
“…Me5 cells have gap junctions that form somato-somatic synapses among small groups of neurons [16,17]. Each neuron is almost entirely covered with processes that radiate from two or more astrocytes (usually astrocytes cover more neurons) [17].…”
Section: The Me5mentioning
confidence: 99%
“…However, this direct approach for the detailed analyses of the features of these electrical contacts has not been further pursued until recently. Curti et al [95] found that electrical coupling is restricted to small clusters of Mes V neurons. They also indicated that connexin-36-containing gap junctions mediated electrical transmission between Mes V neurons [96].…”
Section: Electrical Coupling Promotes Strong Synchronizationmentioning
confidence: 99%